THE NEED OF PARADIGM CHANGE AND MULTICULTURAL LITERATURE IN EARLY CHILDHOOD EDUCATION; THE INDONESIAN CONTEXT - Muna Yusak, Nailil (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2014)
As the home of many ethnic groups, Indonesia is a showcase of diversity. On the one hand Indonesiais benefited in many crucial sectors such as economy and tourism from the rich diversity of its natural and human resources but on the other hand the country is facing a high risk of intergroup friction. The goverment of Indonesia attempted to end social conflict and disintegration in many ways, from interfaith dialogue to military occupation. Despite of all progress, little has been done to find a fundamental resolution. This study examines the importance of paradigm change in understanding conflict. The New Order approach in conflict resolution suggests that conflict is destructive and therefore needs to be avoided. However, conflict can also be constructive and in order to deal with conflict in a constructive way, institutions or organizations must be aware of this two-fold concerns and citizens must be educated in the skill to face conflict. Going deeper in the plea that education constructs a nation, using the same analogy, peace education should also construct a peaceful nation. Finally, this study proposes the use of multicultural literature to reconstruct the notion of conflict through the practice of multicultural education in early childhood education.